Escherichia coli Old and New Insights - Starčič Erjavec, Marjanca (IntechOpen, 2023)
This book illuminates the various aspects of Escherichia coli, including its pathotypes, virulence factors, and antimicrobial resistance. It also presents new insights into the scientometric analysis of the E. coli knowledge landscape, novel molecular diagnostic platforms, novel antimicrobial agents, and E. coli-based DNA amplification-expression technology for the automatic assembly of concatemeric open reading frames and proteins.